2023
DOI: 10.1101/2023.09.19.23295785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in Hepatitis C Virus Seroprevalence and Associated Risk Factors among MSM in Pakistan: Insights from a Community-Based Study

Raza Tirmizi,
Rimsha Munir,
Nousheen Zaidi

Abstract: This community-based cross-sectional study investigates the seroprevalence of the Hepatitis C Virus (HCV) and its associated demographic and behavioral risk factors among the men who have sex with men (MSM) in Pakistan. The study reveals an HCV seroprevalence of 14.86%, significantly higher than global averages for the MSM population. Notably, HCV seroprevalence was associated with age, education level, self-identified sexual orientation, and self-reported HIV status. Furthermore, the study identified several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have reported high HCV seroprevalence among men who have sex with men (MSM) (22)(23)(24). However, only a few studies have undertaken a comparative analysis of sex-based differences among sex workers (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported high HCV seroprevalence among men who have sex with men (MSM) (22)(23)(24). However, only a few studies have undertaken a comparative analysis of sex-based differences among sex workers (25,26).…”
Section: Discussionmentioning
confidence: 99%